The Quality and Outcomes of Care Provided to Patients with Cirrhosis by Advanced Practice Providers. Issue 1 (21st June 2019) - Tapper, Elliot B.; Hao, Shengchen; Lin, Menghan; Mafi, John N.; McCurdy, Heather; Parikh, Neehar D.; Lok, Anna S.
Abstract : Cirrhosis is morbid and increasingly prevalent, yet the U.S. health care system lacks enough physicians and specialists to adequately manage patients with cirrhosis. Although advanced practice providers (APPs) can expand access to cirrhosis‐related care, their impact on the quality of care remains unknown. We sought to determine the effect on care quality and outcomes for patients managed by APPs using a retrospective analysis of a nationally representative American commercial claims database (Optum), which included 389, 257 unique adults with cirrhosis. We evaluated a complication of process measures (i.e., rates of hepatocellular carcinoma [HCC] screening, endoscopic varices screening, and use of rifaximin after hospitalization for hepatic encephalopathy) and outcomes (30‐day readmissions and survival). Compared with patients without APP care, patients with APP care had higher rates of HCC screening (adjusted odds ratio [OR] 1.23, 95% confidence interval 1.19, 1.27), varices screening (OR 1.20 [1.13, 1.27]), use of rifaximin after a discharge for hepatic encephalopathy (OR 2.09 [1.80, 2.43]), and reduced risk of 30‐day readmission (OR 0.68 [0.66, 0.70]). Gastroenterology/hepatology consultation was also associated with improved quality metric performance compared with primary care; however, shared visits between gastroenterologists/hepatologists and APPs were associated with the best performance and lower 30‐day readmissions compared with subspecialty consultation without an APP (OR 0.91 [0.87, 0.95]. Multivariate analysis adjusting for comorbidities, liver disease severity, and other factors including gastroenterology/hepatology consultation showed that patients seen by APPs were more likely to receive consistent HCC and varices screening over time, less likely to experience 30‐day readmissions, and had lower mortality (adjusted hazard ratio 0.57, 95% confidence interval 0.55, 0.60). Conclusion: APPs, particularly when working with gastroenterologists/hepatologists, are associated with improved quality of care and outcomes for patients with cirrhosis.